Stats will do nicely - Kellie Harrington using analytics to help secure Olympic success (2020)
"Since SAS came on board, it has helped me so much with my preparation and it is going to help me qualify for Tokyo at the qualifiers in March in London," Harrington said speaking at a media event which highlighted the benefits of data analytics for elite athletes and coaches.